Relationship between sea surface temperature and the maximum intensity of tropical cyclones affecting Vietnam's coastline - Thanh, Nguyen T.; Cuong, Hoang D.; Hien, Nguyen X.; Kieu, Chanh (International journal of climatology, 2020)
Estimating an upper bound for tropical cyclone (TC) intensity in a given environment is important for TC intensity forecasts and risk management. While theoretical limits for the TC maximum potential intensity have been well examined in previous studies, the actual maximum intensity ( Vmax) that a TC attains in real atmospheric conditions varies from basin to basin and is subject to much more uncertainties. This study examines different empirical relationships between sea surface temperature (SST) and Vmax in the South China Sea that affect Vietnam's coastal region. Using different SST datasets and the TC intensity record from 1982 to 2016, it is shown that Vmax in this area increases slower than the typical linear or exponential function form found in previous studies. Such different dependence of Vmax on SST in the South China Sea is due to the narrow range of SST variation in this region, which is between 24 and 30°C as compared to the range of 15 and 30°C used in previous studies. An alternative functional form based on the natural logarithm of SST is then proposed, which captures better the characteristics of the actual TC maximum intensity in Vietnam's coastal region. Examination of the variability of Vmax also indicates an uptrend of the TC maximum intensity over last 30 years in the South China Sea, which has a potentially large effect on Vietnam's coastal region. This increase of Vmax is consistent with the warmer trend of the SST as projected in the Fifth Assessment by the Intergovernmental Panel on Climate Change (IPCC). The maximum intensity of tropical cyclones (TC) in the South China Sea that could affect Vietnam's coastline increases slower than the typical linear or exponential function form as often used in previous studies. The actual maximum intensity of TCs in the South China Sea indicates an uptrend over last 30 years, which has a potentially large effect on Vietnam's coastal region. The satellite imagery above Typhoon Damrey on November 3, 2017 at 0118 UTC when the typhoon's winds had reached about 65 kts (75 mph). Courtesy of SSAI/NASA GSFC.